2016
DOI: 10.1038/srep33930
|View full text |Cite
|
Sign up to set email alerts
|

Gondwanan conifer clones imperilled by bushfire

Abstract: Global increases in fire frequency driven by anthropogenic greenhouse emissions and land use change could threaten unique and ancient species by creeping into long-term fire refugia. The perhumid and mountainous western half of Tasmania is a globally important refugium for palaeo-endemic, fire intolerant lineages, especially conifers. Reproductive strategy will be crucial to the resilience of these organisms under warmer, dryer and more fire prone climates. This study analysed clonal versus sexual reproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The aggregation index of W. floribunda was comparable with those of other non-liana clonal woody plant species. For example, the Gondwanan conifer species Athrotaxis cupressoides had a mean aggregation index of 0.43 (Worth et al, 2016), while the aggregation index is reported to vary widely, both within species (0.1-0.79: A. curpressoides, Worth et al, 2016) and between species (0.03: Nothofagus pumilio, Mathiasen and Premoli, 2013;0.62: Populus nigra, Chenault et al, 2011). A slightly intermingled distribution pattern of genets was observed in the present study, while clonal patches of W. floribunda seemed to exhibit a lower degree of overlapping distribution (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The aggregation index of W. floribunda was comparable with those of other non-liana clonal woody plant species. For example, the Gondwanan conifer species Athrotaxis cupressoides had a mean aggregation index of 0.43 (Worth et al, 2016), while the aggregation index is reported to vary widely, both within species (0.1-0.79: A. curpressoides, Worth et al, 2016) and between species (0.03: Nothofagus pumilio, Mathiasen and Premoli, 2013;0.62: Populus nigra, Chenault et al, 2011). A slightly intermingled distribution pattern of genets was observed in the present study, while clonal patches of W. floribunda seemed to exhibit a lower degree of overlapping distribution (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion has some analogies with findings for the closely related and similarly fire‐sensitive A. cupressoides open forests on the Central Plateau of Tasmania (Holz et al, ). The collapse of A. cupressoides woodlands and subsequent large‐scale switch to alpine heathland on the Central Plateau, occurred after a single, extreme high‐severity fire in 1960–1961 associated with a historically anomalous drought (Holz et al, ), and these open forests are unlikely to recover due to poor dispersal attributes (Holz et al, ; Worth et al, ). There are some substantive differences, however, in fire regime between these two fire‐sensitive species and their respective ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Cupressaceae taxa in Tasmania have high‐quality fossil pollen and genetic diversity records that provide a long‐term context of the impact of late‐Pleistocene and Holocene fire–human–climate dynamics on Athrotaxis (Fletcher et al, ; Worth et al, , ). Recent Tasmanian paleoecological research has suggested that the intensification of El Niño–Southern Oscillation (ENSO) since the mid‐Holocene led to increase fire activity and associated vegetation change in N and SE parts of the island (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual reproduction occurs via wind-dispersed seed, with seed production occurring in episodic masting cycles every 5 -6 years (Cullen and Kirkpatrick 1988a). However, vegetative reproduction is more common, whereby A. cupressoides regenerates vegetatively via root suckers (Worth et al 2016b). On average, about 60% of stems (ramets) are clonal, and are often aggregated in clusters that arise from the same genet; some genets can produce multiple clusters up to 38 m apart, interspersed with stems from other genets (Worth et al 2016b).…”
Section: Study Speciesmentioning
confidence: 99%
“…One important Tasmanian palaeoendemic species is the iconic conifer Athrotaxis cupressoides D. Don (pencil pine), which is found in montane areas in central and western Tasmania. The species has a limited capacity to disperse by seed, and sexual regeneration appears less common than clonal growth via production of ramets (Worth et al 2016b). The vulnerability of A. cupressoides to fire is demonstrated by the fact that extensive fires during the dry summer of 1960/61 are estimated to have eliminated it from about 10% of its entire range (Corbett 1996;Johnson and Marsden-Smedley 2002;Holz et al 2015).…”
Section: Introductionmentioning
confidence: 99%